Leaching fraction impacts water use efficiency and nutrient losses in maize crop under salt stress - Emanuel D. Freitas; Claudivan F. de Lacerda; Aiala V. Amorim; Jorge F. da S. Ferreira; Carlos A. G. Costa; Alexsandro O. da Silva; Hans R. Gheyi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Although leaching fraction (LF) is used to remove salts from the root zone under conditions of salinity, if miscalculated, it can decrease water use efficiency and lead to major losses of essential nutrients. This study evaluated the water use efficiency, leaf nutrient concentrations in maize plants, and nutrient losses as a function of two ways of determining the LF in maize crop grown in soil columns under salt stress. The experimental design used was completely randomized, with treatments arranged in split plots, with seven replicates. The plots were formed by two methods of determination of LF, and the subplots by four electrical conductivities of irrigation water - ECw (0.5, 2.0, 4.0, and 6.0 dS m-1). The leaching fractions were established according to 1) the formula proposed by Rhoades (RHO) and 2) by applying a LF of 0.15 calculated according to the soil water balance (SWB). The leaf concentrations of N, P, Ca, and Mg were higher in plants under SWB than under RHO method. The leaf concentrations of N, P, and K decreased with increased salinity, regardless of the LF. Adding a LF of 0.15 according to SWB resulted in decreased losses of nutrients and higher physical water productivity, as compared to the RHO. Thus, a more precise determination of the LF is needed to increase economic returns for maize cultivation in semi-arid regions when using brackish water for irrigation.